Antimutagenic, antitumor and estrogen receptor binding activity of the rare plant Shortia galacifolia: An ethnobotanical and chemosystematic approach - Sandra Gray; Brett Lackey; Patricia Tate (Mashhad University of Medical Sciences, 2019)
Objective: Shortia and other members of the Diapensiaceae family have ethnomedicinal history in both Eastern and Western hemispheres. Based on ethnopharmacological and chemosystematic evidence, pharmacological and toxicological bioassays were conducted on the rare plant Oconee Bell, Shortia galacifolia. Materials and Methods: Extracts were examined in assays for antimutagenicity, antitumor and estrogen receptor (ER)-binding activity.  Antitumor activity was assessed by the tumor induction assay (TiA), using Agrobacterium tumefaciens based on its ability to transform plant tissue.  Antimutagenicity was examined using the Ames bacterial reverse mutation test.  Recombinant human ERα and ERβ proteins were utilized to screen extracts for receptor selectivity. Results: All concentrations of extracts inhibited A. tumefaciens-induced tumor formation on potato discs, with the mature rhizome extracts having the most marked inhibition.  All three plant extracts significantly inhibited the formation of histidine-independent revertant colonies after exposure to the mutagen 2-aminoanthracene (2-AA) in the Ames Salmonella mutagenicity assay.  In the ER binding assays, ERβ, but not ERα, displayed affinity for Shortia extracts. Conclusion: Antitumor, ER binding and antimutagenic activities of S. galacifolia extracts were identified using rapid bench-top assays and warrant further investigations.